2013
DOI: 10.1093/jac/dkt327
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus carrying the mecC gene: emergence in Spain and report of a fatal case of bacteraemia

Abstract: We confirm the presence of MRSA carrying the mecC gene in Spain, the ability of this livestock-associated MRSA to cause severe infections in humans and the need to perform culture-based susceptibility testing methods in order to detect these emerging strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…A retrospective study in Spain recently identified five mecC-MRSA isolates among isolates collected from one hospital between 2008 and 2013. In the same work, retrospective screening for mecC among 5,505 human S. aureus isolates received during the same period at the Spanish National Reference Centre for Staphylococci revealed two additional mecC-MRSA isolates (0.036%) (6).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…A retrospective study in Spain recently identified five mecC-MRSA isolates among isolates collected from one hospital between 2008 and 2013. In the same work, retrospective screening for mecC among 5,505 human S. aureus isolates received during the same period at the Spanish National Reference Centre for Staphylococci revealed two additional mecC-MRSA isolates (0.036%) (6).…”
mentioning
confidence: 85%
“…The genetic backgrounds of all the MRSA isolates were investigated by multilocus sequence typing (MLST) (6). The genetic struc-ture of the staphylococcal cassette chromosome mec element (SCCmec) and the presence of Panton-Valentine leukocidin (PVL) virulence factor genes (lukS-PV and lukF-PV) were also determined (2,(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mecC MRSA was isolated in hospital patients from Slovenia [9] , Germany [10] , Republic of Ireland [11] , Denmark [12] , Spain [13] [14] and France [15] . Garcia-Garrote et al [14] reported the first mecC MRSA fatal human case in Spain, a patient with sepsis who died in the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Garrote et al [14] reported the first mecC MRSA fatal human case in Spain, a patient with sepsis who died in the emergency department. In the same study mecC MRSA was reported in 6 other human cases, predominantly in skin and soft tissue infections.…”
Section: Discussionmentioning
confidence: 99%